Toward a Clinical Protocol for Assessing Rod, Cone, and Melanopsin Contributions to the Human Pupil Response - Park, Jason C. (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. To better understand the relative contributions of rod, cone, and melanopsin to the human pupillary light reflex (PLR) and to determine the optimal conditions for assessing the health of the rod, cone, and melanopsin pathways with a relatively brief clinical protocol. METHODS. PLR was measured with an eye tracker, and stimuli were controlled with a Ganzfeld system. In experiment 1, 2.5 log cd/m(2) red (640 ± 10 nm) and blue (467 ± 17 nm) stimuli of various durations were presented after dark adaptation. In experiments 2 and 3, 1-second red and blue stimuli were presented at different intensity levels in the dark (experiment 2) or on a 0.78 log cd/m(2) blue background (experiment 3). Based on the results of experiments 1 to 3, a clinical protocol was designed and tested on healthy control subjects and patients with retinitis pigmentosa and Leber's congenital amaurosis. RESULTS. The duration for producing the optimal melanopsin-driven sustained pupil response after termination of an intense blue stimulus was 1 second. PLR rod- and melanopsin-driven components are best studied with low- and high-intensity flashes, respectively, presented in the dark (experiment 2). A blue background suppressed rod and melanopsin responses, making it easy to assess the cone contribution with a red flash (experiment 3). With the clinical protocol, robust melanopsin responses could be seen in patients with few or no contributions from the rods and cones. CONCLUSIONS. It is possible to assess the rod, cone, and melanopsin contributions to the PLR with blue flashes at two or three intensity levels in the dark and one red flash on a blue background.